Antibacterial and antioxidant activities of endophytic fungi and nettle (Urtica dioica L.) leaves as their host - Salmi, Djouza; Riou, Catherine; Issawi, Mohammad; Titouche, Yacine; Ambrosini, Veronica; Smail-Saadoun, Noria; Abbaci, Hocine; Houali, Karim (Cellular and Molecular Biology, 2021)
Nettle (Urtica dioica L), as a plant rich in biologically active compounds, is one of the most important plants used in herbal medicine. Studies have shown that this plant has antioxidant, antiplatelet, hypoglycemic and hypocholesterolemia effects. In this study, we characterized three Alternaria endophytic fungi isolated from their host U. dioica. We hypothesized that these endophytic fungi can produce new bioactive metabolites, which may possess the bioactive property with potential application in the medical and pharmaceutical industries. The antibacterial activity was evaluated against reference and isolated strains, including Methicillin-Resistant Staphylococcus aureus. A wide range of antimicrobial activities similar to those measured in nettle leaves was detected especially for Alternaria sorghi. Furthermore, the highest antioxidant activity detected with DPPH free radical scavenging was measured for A. sorghi and nettle leaves ethyl acetate extracts. In addition, whereas catalase activity was similar in the three isolated fungi and nettle leaves, total thiol content and superoxide dismutase activity were significantly higher in leaves. A. sorghi showed the best activities compared to other isolated fungi. The characterization and further production of bioactive compounds produced by this endophyte should be investigated to fight bacteria and especially those that develop drug multi-resistance.